Kebijakan Kesempatan Kerja - Budiman Widodo (Universitas Riau, 2011)
This research aims to reveal opportunities for employment in home industries in ruralareas, and the level of income earned from industrial activities of the household and the factorsthat influence it, including: a) the skill factor the craftsmen; b) the allocation of time; c) growth in thenumber domestic industry during the last 5 years. Respondents of this study totaled 163 homeindustries, which include industrial type house hold steamer, pots of house hold industriesand types of carving home industry. Data was collected using questionnaires, interviewsand observation. To find out how much manpower that is absorbed is used cross tabulati-on analysis between the skills and earned income and the allocation of time for each industry. Theresults of this study indicate that the domestic industry to create employment opportunities in ruralareas by increasing the amount of energy absorbed by domestic industrial sector and increasingrural income. The existence indistri house holds in rural areas is a policy alternative employmentopportunities in solving the problem of employment reduction in agriculture sector and reducethe urbanization